Long noncoding RNA, tissue differentiation‐inducing nonprotein coding RNA is upregulated and promotes development of esophageal squamous cell carcinoma. Issue 8 (2nd February 2016) - Xu, Y.; Qiu, M.; Chen, Y.; Wang, J.; Xia, W.; Mao, Q.; Yang, L.; Li, M.; Jiang, F.; Xu, L.; Yin, R.
Summary: Esophageal squamous cell carcinoma (ESCC) is one of the major causes of cancer death worldwide, especially in Eastern Asia. Due to the poor prognosis, it is necessary to further dissect the underlying mechanisms and explore therapeutic targets of ESCC. Recently, studies show that long noncoding RNAs (lncRNAs) have critical roles in diverse biological processes, including tumorigenesis. Increasing evidence indicates that some lncRNAs are widely involved in the development and progression of ESCC, such as HOTAIR, SPRY4‐IT1 and POU3F3. An emerging lncRNA, tissue differentiation‐inducing nonprotein coding RNA (TINCR), has been studied in human cutaneous squamous cell carcinoma and has critical biological function, but its role in ESCC remains unknown. Here, we evaluated the expression profile of TINCR and its biological function in ESCC. In a cohort of 56 patients, TINCR was significantly overexpressed in ESCC tissues compared with paired adjacent normal tissues. Further, in vitro silencing TINCR via small interfering RNA (siRNA) inhibited the proliferation, migration and invasion of ESCC cells. Meantime, siRNA treatment induced apoptosis and blocked the progression of cell cycle. Taken together, our study suggests that TINCR promotes proliferation, migration and invasion of ESCC cells, acting as a potential oncogene of ESCC.